High‐Grade Gastrointestinal Neuroendocrine Carcinoma Management and Outcomes: A National Cancer Database Study - Alese, Olatunji B.; Jiang, Renjian; Shaib, Walid; Wu, Christina; Akce, Mehmet; Behera, Madhusmita; El‐Rayes, Bassel F. (The oncologist (Dayton, Ohio), 2019)
Background High‐grade neuroendocrine carcinomas are rare in the gastrointestinal tract. However, treatment patterns and outcomes have not been well described. Subjects, Materials, and Methods The National Cancer Database was analyzed. The primary objective was to describe the clinical outcomes and identify prognostic factors. Univariate and multivariate analyses were done to identify factors associated with patient outcome. Results A total of 1,861 patients were identified between 2004 and 2013. The mean age was 63 years (standard deviation ±13). The majority of the patients (78.1%) were non‐Hispanic whites. The most common primary sites were pancreas (pancreatic neuroendocrine tumor [PNET] = 19.4%), large intestine (18.1%), esophagus (17.8%), and rectum (15.5%). Stage at presentation was I (6.6%), II (10.5%), III (18%) and IV (64.6%). Only 1.6% of the patients had brain metastases. Surgical resection was the primary therapy in 27.9%, and their median overall survival (OS) was 13.3 months. Patients treated with palliative chemotherapy had a median OS of 11.2 months, compared with 1.7 months for untreated patients. The median OS for high‐grade PNET was 6 months, compared with 9.9 months for other high‐grade gastrointestinal neuroendocrine carcinomas (HG GI NEC). On univariable analysis, age < 65 years (hazard ratio [HR] 0.72; 0.66–0.8; p < .001) and treatment at an academic center (HR 0.88; 0.79–0.99; p < .034) were associated with improved survival. Multivariable analysis confirmed prognostic advantage of treatment at an academic center. Conclusion This is the largest series of HG GI NEC. Most patients present with metastatic disease, and overall survival remains poor. Treatment at an academic center, younger age, and use of chemotherapy were associated with improved survival. Multiagent chemotherapy was found to be associated with superior survival compared with single‐agent chemotherapy, which was superior to no chemotherapy. Temporal sequences of chemotherapy, surgery, and radiation administration were not found to be associated with survival differences on multivariable analysis. Implications for Practice Management of patients with high‐grade gastrointestinal neuroendocrine carcinomas (HG GI NEC) is based on experience with small‐cell lung cancer. In this retrospective review, most patients had advanced disease and pancreatic primary had worse outcomes. Treatment at an academic center, younger age, and use of chemotherapy are associated with improved survival. Patients with early‐stage disease treated with resection alone had inferior outcomes compared with patients who received neoadjuvant or adjuvant therapy, suggesting that micrometastases contribute to poor surgical outcomes. The relatively high proportion of positive surgical margin favors downstaging with neoadjuvant therapy to improve resection and lower the risk of systemic recurrence. 摘要 背景。高级别神经内分泌肿瘤在胃肠道领域很罕见。然而，人们尚未很好地描述治疗模式及预后。 受试者、材料和方法。我们对国家癌症数据库进行分析。主要目标为描述临床预后并识别预后因素。为了识别与患者预后相关的因素，我们执行了单变量和多变量分析。 结果。在 2004 年至 2013 年期间，一共找到 1 861 名患者。平均年龄为 63 岁(标准差 ±13 岁)。大多数患者 (78.1%) 为非西班牙裔白人。最常见的好发部位为胰腺 [胰腺神经内分泌肿瘤 (PNET)= 19.4%]、大肠 (18.1%)、食道 (17.8%) 和直肠 (15.5%)。患者出现症状的分期为 I 期 (6.6%)、II 期 (10.5%)、III 期 (18%) 和 IV 期 (64.6%)。仅有 1.6% 的患者出现脑转移。手术切除为首选治疗措施，占 27.9%，患者的中位总生存期 (OS) 为 13.3 个月。接受姑息化疗的患者的中位 OS 为 11.2 个月，而未经治疗的患者的中位 OS 为 1.7 个月。高级别 PNET 的中位 OS 为 6 个月，而其他高级别胃肠道神经内分泌肿瘤 (HG GI NEC) 的中位 OS 为 9.9 个月。在单变量分析中，年龄 < 65 岁 [风险比 (HR)0.72；0.66–0.8；p < 0.001]和在学术中心接受治疗(HR 0.88；0.79–0.99；p < 0.034)与延长生存期相关。多变量分析确认了在学术中心接受治疗的预后优势。 结论。这是最大系列的HG GI NEC。大多数患者出现了转移性疾病，总生存期仍然很短。在学术中心接受治疗、年龄较小以及采用化疗均与延长生存期相关。我们发现，与优于不采用化疗的单药剂化疗相比，多药剂化疗与更长的生存期相关。我们未发现化疗、手术和放疗的时间顺序与多变量分析中的生存期差异相关。 实践意义:高级别胃肠道神经内分泌肿瘤 (HG GI NEC) 患者的治疗以小细胞肺癌方面的经验为依据。在本次回顾性调查中，大多数患者患有晚期疾病，原发性胰腺疾病患者的预后较差。在学术中心接受治疗、年龄较小以及采用化疗均与延长生存期相关。与接受新辅助治疗或辅助治疗的患者相比，仅接受切除术治疗的早期疾病患者具有较差的预后，这表明微小转移会导致手术效果不好。手术切缘阳性比例相对较高，这促进了采用新辅助治疗降期，从而改进切除术并降低全身复发的风险。 The analysis presented in this article provides a guide to health care providers for the management of gastrointestinal high‐grade neuroendocrine carcinoma, based on data available to date.